Drop shipping in the supply chain: fiqh perspective - Busari, Saheed Abdullahi; Zakariyah, Habeebullah; Aminu, Sikiru Olanrewaju (Springer International Publishing, 2021)
Abstract. Drop shipping entails movement of goods where a dropshipper as entity A, sells goods that are physically stocked with entity B on a retail basis to a consumer using the online networking system. In Shari’ah, the permissibility of such business arrangement revolves around a fundamental concept of not selling what you do not own. There also exist information asymmetry between the parties where only the retailer merchant has more information than both the seller and the customer. Given its prevalence and increase patronage by Muslims, this study examined the permissibility of the dropshipping using juristic adaptation (Taky¯ıf Fiqh) to ascertain the Shar¯ı’ah compliance of the existing model. Analysis of the Shariah compliant issues in the transaction cycle show that the existing dropshipping model is not fully compliant with the Shariah. Thus, alternative Shari’ah compliant contract in Wak¯alah, Salam and Parallel Salam are proposed to validate the dropshipping model for entrepreneurs who opt for Shari’ah compliant approach